2018
DOI: 10.1002/cphc.201800151
|View full text |Cite|
|
Sign up to set email alerts
|

Photochemical Formation of Cyclobutane Pyrimidine Dimers in DNA through Electron Transfer from a Flanking Base

Abstract: Electron transfer (ET) to a pyrimidine base from external moieties is a common step involved in the quenching or repair of the cyclobutane pyrimidine dimer (CPD). In contrast, we present a pathway that is initiated by an ET from a flanking guanine base to a pyrimidine base, leading to the formation of a CPD. We studied a T5mCG sequence with a methylated cytosine and our results demonstrate that the pathway involves the formation of an exciplex and intersystem crossings. This pathway also provides an explanatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…Although the above‐mentioned studies assumed that CPD enhancement by 5mC occurs in the singlet state, we examined the corresponding mechanism in the triplet manifold because the free energy profile toward CPD formation in the singlet state showed a slightly higher barrier for TmCG than TCG owing to the bulky methyl group of 5mC [8] . In that study, the CPD forming pathway we found was initiated from a dark CT state, but the pathway demonstrated here is initiated from bright ππ* excitation.…”
Section: Resultsmentioning
confidence: 78%
See 3 more Smart Citations
“…Although the above‐mentioned studies assumed that CPD enhancement by 5mC occurs in the singlet state, we examined the corresponding mechanism in the triplet manifold because the free energy profile toward CPD formation in the singlet state showed a slightly higher barrier for TmCG than TCG owing to the bulky methyl group of 5mC [8] . In that study, the CPD forming pathway we found was initiated from a dark CT state, but the pathway demonstrated here is initiated from bright ππ* excitation.…”
Section: Resultsmentioning
confidence: 78%
“…Starting from the T 1 minimum we reached, we carried out restrained optimizations, adding 5mC into the QM region. Here, the distance between the C6 atoms of 5mC and thymine base was used as a reaction coordinate (Figure 3 A) because the pathway leading to CPD in the triplet manifold is known to undergo a biradical intermediate ( 3 BR), which has a single covalent bond between the C6 atoms of the two constituting bases [8, 10, 22, 23] . During these restrained optimizations, we observed a surface crossing between T 1 and the ground state, so we used linear response coupled cluster method of second order (CC2) [14] with def2‐SVP instead of ADC(2)/def2‐SVP for these optimizations because, although ADC(2) more correctly describes surface crossings between excited states, CC2 displays superior performance in describing surface crossings between the ground and excited state than ADC(2) [15, 16] .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the future, we plan to study the whole SPP formation process and quantitatively establish the free energy penalty for CPD formation in the spore environment. Moreover, the possible influence of charge‐transfer states involving flanking nucleobases on the SPP formation remain to be studied [51–54] …”
Section: Resultsmentioning
confidence: 99%